. Cultural, economic, and educational predictors of school exit exam scores in Azerbaijan - G. A. Alasgarova (Obrazovanie i Nauka)
Introduction. The Ministry of Education (MOE) of the Azerbaijan Republic requires that students take an exit exam at the end of secondary schooling. The school exit exam (SEE) is administered to graduating students in 11th grade (i.e., high school equivalent) in three core subjects: (1) mathematics, (2) instructional language, and (3) foreign language. The State Examination Centre (SEC) has administered the SEE for over five years and recently changed the format, impacting university admissions (UA). In 2019, admission to a university was in two stages: (1) the SEE and (2) the university admissions exam. The current study used publicly available SEC data (N = 73) from Azerbaijan’s 2019/2020 academic year by region.Aim. The current research aims to examine the cultural, economic, and educational predictors of the school exit exam (SEE) in Azerbaijan’s cities/regions according to the 2020 data. The article intends to demonstrate the relationship between economic, educational, and cultural precursors for successful versus unsuccessful SEE results. Methodology and research methods. This correlational study used Multivariate (MANOVA) and Univariate (ANOVA) Analyses of Variance (RQ1) and Multiple Regressions (RQ2 and RQ3).Results. For cultural predictors of the SEE, the Northern region had significantly higher Instructional Language (p = .010), English (p = .020), and Total scores (p = .010) compared to other regions. For economic indicators of the SEE, the average monthly salary was significantly predictive of Foreign Language (p = .035). For educational variables, the percentage of outstanding graduating students was predictive of all outcomes (p < .000 for all).Scientific novelty and practical significance. Literature supports that the percentage of outstanding students and a family’s annual income are strong positive predictors of SEE scores for all four D.V.s. Thus, this study claims that regions with exceptional academic performance and high family income tend to produce higher SEE scores. This substantive finding highlights the inter-rater reliability between the MOE and the SEC, as academic achievement is assessed by the MOE and the exit exam by the SEC.